Efektivitas Pendayagunaan Zakat Produktif dalam Pemberdayaan Ekonomi Mustahik: Studi pada Baznas Kota Surabaya - Siti Mar’atus Sholihah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is a qualitative descriptive research that aims to determine the effectiveness of the utilization of productive zakat in the empowerment of the mustahik economy. The data collection technique uses observation, interviews, and documentation. The results of this study show that the concept of utilizing productive zakat in the empowerment of mustahik economy implemented by BAZNAS Surabaya is outlined in several programs, namely in the form of providing business capital assistance both individually and in groups, providing job skills training, and providing work tool assistance. As for the effectiveness indicators, the theory from Ni Wayan Budiani is used, namely: the accuracy of program targets, program socialization, program objectives, and program monitoring. It can be seen that the indicators of the accuracy of program targets and have been effective, while the indicators of program socialization, program monitoring, and program objectives can be said to be ineffective.